2008
DOI: 10.1308/003588408x285883
|View full text |Cite
|
Sign up to set email alerts
|

The Case for Standardisation of the Management of Gallstones Spilled and not Retrieved at Laparoscopic Cholecystectomy

Abstract: RESULTS Eighty-two surgeons completed the questionnaire. Only half of surgeons inform patients when gallstones are spilled. Less than 30% of surgeons inform general practitioners (GPs) of this complication, when it occurs. Less than a quarter of surgeons include this information in the consent literature provided to patients. CONCLUSIONS We recommend that trusts review their policy towards spilled stones either by local audit or adopt the guidance given by the UK Healthcare Commission. While some surgeons fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 5 publications
1
26
0
Order By: Relevance
“…In a survey conducted by Mullerat [7], 80% of surgeons don’t have possibility of lost gallstones as part of informed consent. In our survey 55% participants agreed that the patient should be informed prior to surgery regarding possibility of lost gallstones as part of the informed consent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a survey conducted by Mullerat [7], 80% of surgeons don’t have possibility of lost gallstones as part of informed consent. In our survey 55% participants agreed that the patient should be informed prior to surgery regarding possibility of lost gallstones as part of the informed consent.…”
Section: Discussionmentioning
confidence: 99%
“…For some surgeons the rarity of complications dismisses the prospects of converting the LC to an open procedure for retrieving the spilled stones, while for others the seriousness of complications demands that every effort be made to retrieve all gallstones spilled during the procedure. Mullerat [7] reported that only a fifth of surgeons include this phenomenon in the informed consent and only half the surgeons inform the patients in case the stones are lost during LC. They observed that informing the patients may aid in the diagnosis of the complications if in case they occur, but can also result in unnecessary anxiety and repeated examinations for rare complications.…”
Section: Introductionmentioning
confidence: 99%
“…The UK Healthcare Commission has advised one group of surgeons 16 that the risk and possible complications of spilled gallstones should be part of informed consent and that if this does occur and the stones are not retrieved, the patient and their general practitioner should be informed.…”
Section: Other Complicationsmentioning
confidence: 99%
“…As with spilt gallstones,5 every effort must be made to identify and retrieve appendicoliths at the index operation. Retained appendicoliths and gallstones can act as niduses for infection, and thus cause symptoms at a later stage.…”
Section: Discussionmentioning
confidence: 99%